Immunopathology, Diagnosis, and Management of Hypersensitivity Pneumonitis - Selman, Moisés; Buendía-Roldán, Ivette (Seminars in Respiratory and Critical Care Medicine, 2012)
Hypersensitivity pneumonitis (HP) is an inflammatory interstitial lung disease caused by a wide variety of organic particles and certain small-molecular weight chemical compounds that provoke an exaggerated immune response in susceptible individuals. The clinical manifestations are heterogeneous and have been classically described as acute, subacute and chronic. The chronic form has an insidious onset over a period of months or years, with progressive dyspnea and often evolves to fibrosis. The pathology is characterized by a bronchiolocentric interstitial mononuclear cell infiltration, nonnecrotizing poorly formed granulomas, cellular pneumonitis and variable degrees of fibrosis. However, morphological diagnosis of HP is complicated because the subacute/chronic forms may be difficult to distinguish from idiopathic pulmonary fibrosis/usual interstitial pneumonia and nonspecific interstitial pneumonia. In general, diagnosis of HP represents a challenge for clinicians that need to weigh a constellation of clinical, laboratory, radiographic and (when available) pathological evidence for each patient to assess the certainty of the diagnosis. The cornerstone of therapy is antigen avoidance. Although clinical trials are scanty, corticosteroids are usually indicated based upon expert opinion. In this review we summarize the current evidence regarding the diagnostic criteria and therapeutic strategies as well as the immunopathological mechanisms putatively implicated in the development of the disease.
Keywords: hypersensitivity pneumonitis; extrinsic allergic alveolitis; lung fibrosis